Analisis Kandungan Fitokimia, Fenolik, Aktivitas Antioksidan, dan Toksisitas Daun Kumis Kucing - Aspasia, Ariadne Calista; Swantari, Ni Made; Ferdinal, Frans; Yulianti, Eny (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2026)
Introduction: Orthosiphon stamineus (cat’s whiskers) is a traditional medicinal plant rich in bioactive compounds and has potential as a natural antioxidant. However, comprehensive studies linking its phytochemical composition with antioxidant activity and toxicity remain limited. Purpose: This study aimed to evaluate the phytochemical profile, total phenolic content, antioxidant activity, and toxicity of O. stamineus leaf extract. Methods: The study was conducted experimentally using in vitro and bioassay approaches. Phytochemical screening was performed to identify secondary metabolites. Total phenolic content was determined using the Folin–Ciocalteu method with gallic acid as the standard. Antioxidant activity was assessed using DPPH, ABTS, and FRAP assays, while toxicity was evaluated using the Brine Shrimp Lethality Test (BSLT). Results: The results showed that the extract contained various secondary metabolites, including alkaloids, flavonoids, coumarins, tannins, phenolics, terpenoids, steroids, glycosides, quinones, anthocyanins, and cardiac glycosides. The total phenolic content was 43.02 mg GAE/g DW. The IC₅₀ values for DPPH and ABTS were 116.29 µg/mL and 123.22 µg/mL, respectively, indicating moderate antioxidant activity. The FRAP value was 337.9 µmol/L. Toxicity testing yielded an LC₅₀ value of 653.6 µg/mL, indicating low toxicity. Conclusion: O. stamineus leaf extract shows potential as a natural antioxidant source with low toxicity, supporting its prospective application in pharmaceutical and health-related fields.